Novas substâncias isoladas de Evolvulus linarioides Meisn. (Convolvulaceae) - Queiroga, Cinthia Silveira (2012)
The Caatinga biome is a promising source of biomolecules of plant origin. In Paraíba, Northern Brazil, the Pico do Jabre state park is the largest area of total protection and conservation included in this biome, where is possible to find the species Evolvulus linarioides Meisn, a small blue-flowered herb, distributed at lower altitudes and rocky outcrops. This work describes the results obtained in the phytochemical study of E. linarioides. The dried and pulverized plant material was subjected to extraction and chromatographic techniques in order to isolate some chemical constituents. The structural identification of these constituents was performed by spectroscopic methods, such as Infrared (IR), 1H and 13C NMR (uni and bidimensional), mass spectrometry and comparisons with literature data. A novel sesquiterpene, 5α-hydroximethyl-cariophyl-3(4)-en-8β-5α-diol, to which the name linariofileno was assigned, was obtained from the dichloromethane extract; from the ethyl acetate extract, two chromones were isolated: cnidimol C and 5,7-dihydroxy-2-hydroxymethyl-4H-1-benzopiran-4-one-9-O-β-glucoside, being reported for the first time in literature and assigned the name cnidimol C glucoside. These results emphasize the importance of this work to a better knowledge of the secondary metabolites s profile of plant origin in the Caatinga biome. Furthemore, it advances in the future perspective of interdisciplinary studies through the evaluation of biological properties of these novel molecules isolated and identified from the Convolvulaceae family.